Adoption of Vaccination Against Newcastle Disease by Rural Poultry Women Farmers in the North Central Zone of Nigeria - Saliu, O.J.; Sanda, M.E.; Audu, S.I. (International Journal of Poultry Science, 2009)
Newcastle disease is now claimed to be responsible for 70-80% of annual death in village chickens. Losses in hundreds of poultry birds of various ages and sexes in Ijumu local government area in the north central zone of Nigeria is attributed to the disease. The prevalence is always at its peak during the dry season (Hamattan) of every year in the last decade. Live Newcastle vaccines such as intra ocular, B1 strain, LaSota and Komorov have been produced by National Veterinary Research Institute (NVRI) vom to prevent the occurrence of the disease. Structured questionnaire was designed to quest for adoption of the Newcastle vaccination from 107 poultry women farmers in the study area. The level of awareness of the vaccination was about 70% while, only 11.21% adopted the vaccination alone and 34.58% adopted both the vaccination and ethnoveterinary treatments. Age contributed positively (14.9%) but not significantly to the adoption of the vaccination. This implies that the adoption of the vaccination still need much extension service effort for improvement. This study recommends that both private and public extension outfit should make complementary effort to improve the adoption of the vaccination by the rural women.